Effect of blade’s constructional and operational features on cutting torque requirement in context of henna harvesting - Sonawane, Shital; Mehta, A K; Meena, S S; Panwar, N L; Roul, A K (Journal of Postharvest Technology, 2022)
The present study was focused on the investigation of effect of various blade and operational parameters for selection of efficient cutting system for henna harvester. The effect of blade type, cutting speed and diameter of henna stem were observed on the cutting torque and specific cutting energy at constant moisture content. The experimental was conducted with three parameters i.e., blade type, cutting speed and henna stem diameter to find the effect on cutting torque. The three-carbide tipped circular saw blades was selected under study were showed good torque characteristics and demanded lesser torque compared to the regular brush cutter blade. The average cutting torque values for three carbide tipped blades lies between 3.12- 4.18 N.m, while average cutting torque for regular brush cutter blade was 18.82 N.m. The cutting torque was having inverse relation with the rotational cutting speed. The average cutting torque at lowest rotational cutting speed i.e., at 600 rpm was 9.18 N.m while at highest rotational speed i.e., 1200 rpm it was 6.31 N.m. It was observed that at higher rotational speed i.e., at 1000 and 1200 rpm cutting operation was somewhat noisy due to speed induced vibrations. The cutting torque showed a linearly proportional relationship with diameter of stalk. The specific power requirement for regular brush cutter blade was highest compared to carbide tipped blades. Finally, based on the results the carbide tipped blade with 120 teeth at 600-800 rpm was recommended for the henna harvester.